Optimal and Stability Analysis of the Co-Infections Disease Mathematical Model (Journal of Nonlinear Modeling and Analysis, 2025)
A co-infection of a human or a pig with human influenza or COVID-19 strains and H5N1 strain may result in a pandemic strain, causing a widespread deadly pandemic. In this paper, we consider a new class of co-infectionsdisease epidemic models for a rapid and slow virus. We study the transmissionthreshold by analyzing the basic reproduction number. The equilibrium pointsfor the model are derived, and their local stability is analyzed with suitableassumptions on the model parameters. Understanding the model parametersis one of the prime subjects in this research work. Therefore, the sensitivityof essential parameters is investigated. Moreover, the optimal control problemfor the proposed model is considered, and first-order optimality conditions arederived. Finally, numerical simulations indicate the effects of the model’s basicreproduction number and control variables.
Keywords: Co-infections model; stability analysis; basic reproduction number; optimal control.